2012
DOI: 10.1155/2012/369567
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Rainfall Episodes in the Eastern Northeast Brazil Linked to Large-Scale Ocean-Atmosphere Conditions in the Tropical Atlantic

Abstract: Relationships between simultaneous occurrences of distinctive atmospheric easterly wave (EW) signatures that cross the south-equatorial Atlantic, intense mesoscale convective systems (lifespan > 2 hour) that propagate westward over the western south-equatorial Atlantic, and subsequent strong rainfall episodes (anomaly > 10 mm·day−1) that occur in eastern Northeast Brazil (ENEB) are investigated. Using a simple diagnostic analysis, twelve cases with EW lifespan ranging between 3 and 8 days and a mean velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 47 publications
(57 reference statements)
3
54
0
12
Order By: Relevance
“…Rainfall variability due to the other systems such as the easterly wave disturbances (EWs) and upper tropospheric cyclonic vortices (TCVs) is out of the scope of the present analysis. The EWs affect eastern NEB during austral winter (Yamazaki and Rao, 1977;Kouadio et al, 2012;Hounsou-Gbo et al, 2015) and the TCVs are more common during austral summer and affect most of NEB (Kousky and Gan, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall variability due to the other systems such as the easterly wave disturbances (EWs) and upper tropospheric cyclonic vortices (TCVs) is out of the scope of the present analysis. The EWs affect eastern NEB during austral winter (Yamazaki and Rao, 1977;Kouadio et al, 2012;Hounsou-Gbo et al, 2015) and the TCVs are more common during austral summer and affect most of NEB (Kousky and Gan, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…When these disturbances propagate toward the eastern NEB they can generate large rainfall amounts specially over the eastern coastal areas (e.g. Gomes et al, 2015;Hounsou-gbo et al, 2015;Kouadio et al, 2012). Rao et al (1993) found that the seasonal variation of the intensity and position of the subtropical high in the South Atlantic Ocean modulates coastal winds during the fall and winter.…”
Section: Factors Influencing Precipitation Regimesmentioning
confidence: 99%
“…The convection activity is most intense in the equatorial western Atlantic region (near eastern coastland of Brazil) in autumn 1999. The convection activity associated with disturbances formed in the west African coastland reached eastern Brazil owing to the intensification of easterly trade winds, as suggested by recent observational studies (Kouadio et al , ). On the other hand, the convection activity is located in the tropical eastern Atlantic region in autumn 1998 (Figure (a)).…”
Section: Resultsmentioning
confidence: 71%